2015
DOI: 10.1167/15.16.14
|View full text |Cite
|
Sign up to set email alerts
|

Functional decomposition of the human ERG based on the discrete wavelet transform

Abstract: The morphology of the electroretinogram (ERG) can be altered as a result of normal and pathological processes of the retina. However, given that the ERG is almost solely assessed in terms of its amplitude and timing, defining the shape of the ERG waveform so that subtle, physiologically driven, morphological changes can be systematically and reproducibly detected remains a challenging problem. We examined if the discrete wavelet transform (DWT) could meet this challenge. Normal human photopic ERGs evoked to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 50 publications
5
41
1
2
Order By: Relevance
“…As an additional detail to consider, the DWT is not a shift-invariant transform, in that shifting (translating) the complete ERG waveform in time can affect the energy of the presumed PhNR time-frequency bin. However, in contrast to the results reported for analysis of the a- and b-waves [16], preliminary evidence indicated that the effect of shifting the waveform on the PhNR energy (11 Hz, 60 – 120 ms time-frequency bin) was minimal. As such, only non-shifted data (i.e.…”
Section: Methodscontrasting
confidence: 94%
See 4 more Smart Citations
“…As an additional detail to consider, the DWT is not a shift-invariant transform, in that shifting (translating) the complete ERG waveform in time can affect the energy of the presumed PhNR time-frequency bin. However, in contrast to the results reported for analysis of the a- and b-waves [16], preliminary evidence indicated that the effect of shifting the waveform on the PhNR energy (11 Hz, 60 – 120 ms time-frequency bin) was minimal. As such, only non-shifted data (i.e.…”
Section: Methodscontrasting
confidence: 94%
“…1. The DWT was computed in MATLAB according to standard techniques that are described in detail elsewhere [16]. In brief, DWTs were obtained using the fast wavelet transform algorithm of Mallat [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations